STRUCTURE AND MAGNETIC-PROPERTIES OF GD1-XSRXFEO3-DELTA COMPOUNDS - KIM, CS; UM, YR; PARK, SI; JI, SH; OH, YJ; PARK, JY; LEE, SJ; YO, CH (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 1994)
The perovskite type Gd1-xSrxFeO3-delta (x = 0.0, 0.25, 0.5, 0.75 and 1.0) system has been studied by X-rays, Mohr's salt analysis, and Mossbauer spectroscopy. From the results of X-ray diffraction measurement the structure of the Gd1-xSrxFeO3-delta system is orthorhombic with x values of 0.0, 0.25 and 0.5, and cubic with the x values of 0.75 and 1.0. Mossbauer spectra of Gd1-xSrxFeO3-delta have been taken at various temperatures ranging from 13 to 800 K. Analysis of Mossbauer spectra for this system demonstrated the existence of the mixed valence states of iron and the coordination state of Fe3+ and Fe4+ ions. The Neel temperature decreases linearly with Sr concentration, suggesting that the superexchange interaction for Gd-O-Fe link is stronger than that for Sr-O-Fe link.
Keywords: MOSSBAUER